Personal students' resources as an academic quality indicator in a higher education system - Teslenko, Vita; Petrunko, Olha; Петрунько, Ольга Володимирівна (Scientific Center of Innovative Researches OÜ, 2020)
The phenomenon of academic integrity is considered as a factor in the optimal functioning of the higher education system in terms of psychological approach. The acquisition of personal resources by the students is an evidence of such functioning as a “result of the result” in the possibilities of expanding the framework of personal functioning
Keywords: psychological approach; academic integrity; teaching; student; education